A Farsul e a luta por reforma agrária: violência de classe e marginalização dos movimentos sociais do campo no Rio Grande do Sul (1962) - Nardy, Flávio Correia (2014)
The struggle for Land in Brazil, especially in the early 1960s, passed through deep transformations, that had strong links with the country side modernization process experience dafter the Second World War and the shift of U.S National Policy for Latin America. The changes on this historical period interfere in the relations of the world of work in rural areas, implying a higher disciplining of workers in the field and a forced migration to urban areas, through the rural exodus. These changes cause a reaction of the peasantry, who in an organized manner starts to claim the Agrarian Reform in an attempt to ensure their survival as a class .At this juncture, agrarian dominant classes are reoriented tactically disputing the symbolic field of historical category of Agrarian Reform, ensuring the perpetuation of large land ownership, their source of power. However, throughout this process, there was an intense political struggle over access to land ownership, in which the conflict between rural classes will be established, in giving new structure and dynamics of social class of the country side and leaving deep marks in their class-identities This relationship that is historical, however, would not occur without the intermediation and political participation of the state, which started to provide conditions for these changes could actually be implemented. However, differences occurred between public policies and interests of large and owners. They did not give up of the defense of private property. They tried to give another purpose to these measures, advocated agrarian reform, since it was held from the public lands, mainly in the Midwest and North of the Country. In RS, the large landowners organized by FARSUL have not gone far away from these changes. They were protagonists of the defense of this project, even more than in the state since 1962, the social movements of landless farmers erupted by organizing camps to pressure the government to expropriate some agricultural areas. In reaction, the rural Entity sought to destabilize the social movements through different tactics of violence and criminalization. They directed pressure on the state government to interfere on the mobilizations. The great landowners, unhappy with the state public policies for Agrarian Reform, had organized what they called the "ruralist movment", aiming to gain political power of the state and ensure that candidates were elected to defend their class interests. The conflict initiated by the camps and by the expropriation of farms in the state gave new meaning to the relationship between social classes in the country side and brought new challenges to the way they are related to the political power of the State. This research included Bag FAPERGS-CMH/CAPES.